Voyage et récit de vie dans La Kermesse de Daniel Poliquin - Horányi, Lilla (Verbum – Analecta Neolatina, 2020)
The paper presents an analysis of different meanings of travelling in Daniel Poliquin’s La Kermesse (2006) which deals with the adventures of Lusignan who, despite his ambitious plans, remains captive of his own imagination. We will identify four types of “migration”: changing social class, geographic mobility, alternation of past and present, journeys of the imagination. Our work will also study the combination of these elements in order to show that to the main character telling other people’s stories means telling his own story.